Senior high school students’ learning styles and experiences in the emergency remote teaching - Juárez Díaz, Catalina; Hinojosa Hernández, Emmanuel (Revista de Estilos de Aprendizaje, 2021)
Nowadays Mexican senior high school institutions are promoting temporally emergency remote teaching. Even though the instructional shift is just temporal, it is advisable to implement technology in education, consider student needs, learning styles, and promote student autonomy in the online learning experiences, Moreover, to include the teacher, the social, and the cognitive presences in the community of inquiry. This qualitative study aimed to analyze senior high school students’ online learning experiences in relation to their learning styles. The sampling process was voluntary and consists of 37 participants. The results show predominance of theorist students, followed by the pragmatists, and finally, activists. Favorable learning experiences involved teachers using appropriate strategies and materials to promote learning. Negative online learning experiences were due to students’ lack of understanding and interaction, as well as teachers’ lack of explanation, reinforcement, and feedback, which reflect the lack of cognitive and teacher presence and omission of elements in online learning experiences that address the particularities of students regarding their learning styles.